A study of stellar population of intermediate-age globular cluster NGC 2249 - Li, Zhongmu; Spurzem, Rainer; Mao, Caiyan; Ma, Yingxin; Deng, Yangyang (Results in Physics, 2020)
The Large Magellanic Cloud (LMC) star cluster NGC 2249 has been found to exhibit an extended main-sequence turn-off (eMSTO) in the color-magnitude diagram (CMD) derived from the data of the Hubble Space Telescope (HST). Such CMDs can potentially be explained via a spread of stellar age or rotation rate of single-aged stars, leading to a confusion of its stellar population type. In this work, we use different combinations of age spread (A), rotation (R), and binarity (B) to study the stellar population of this cluster, via a deep HST CMD. Because binaries are commonly observed in star clusters, three models of this study take binaries into account. We finally derive the best-fit stellar population parameters, i.e., metallicity (Z=0.008), age (0.7-1.0Gyr), reddening (E(B-I)=0.52-0.55mag), distance modulus (18.54-18.57mag), binary fraction (50%), rotating star fraction (0-50%), and star formation history mode for NGC 2249. We find that both age spread (A+B or A+R+B) and rotating stars (R+B) can reproduce the main CMD features well, while rotation alone does not reproduce the detailed eMSTO morphology. This suggests that an age spread of 200Myrs is needed to form the eMSTO of cluster NGC 2249, even if stellar rotation is taken into account. Dynamical simulation could be useful for revealing the origin of the eMSTO.